2, 1, 3‐benzothiadiazole‐5, 6‐dicarboxylicimide based semicrystalline polymers for photovoltaic cells. Issue 24 (22nd September 2016) - Nguyen, Dat Thanh Truong; Kim, Taehyo; Li, Yuxiang; Song, Seyeong; Nguyen, Thanh Luan; Uddin, Mohammad Afsar; Hwang, Sungu; Kim, Jin Young; Woo, Han Young
ABSTRACT: Two semicrystalline low band gap polymers based on highly electron‐deficient 2, 1, 3‐benzothiadiazole‐5, 6‐dicarboxylicimide (BTI) were synthesized by considering the chain planarity via intrachain noncovalent coulombic interactions. The thiophene‐BTI and thienothiophene‐BTI based PPDTBTI and PPDTTBTI have a low band gap (∼1.5 eV) via strong intramolecular charge transfer interaction, showing a broad light absorption covering 300∼850 nm. Semicrystalline film morphology was observed for both polymers in the grazing incidence wide angle X‐ray scattering measurements. Interestingly, PPDTBTI showed a pronounced edge on packing structure but PPDTTBTI showed predominantly a face on orientation in both pristine and blend films. Different packing patterns influenced significantly the charge carrier transport, recombination and resulting photovoltaic characteristics. The best power conversion efficiency was measured to be 5.47% for PPDTBTI and 6.78% for PPDTTBTI, by blending with the fullerene derivative, PC71 BM. Compared to the PPDTBTI blend, PPDTTBTI: PC71 BM suffered from the lower open‐circuit voltage but showed the substantially higher hole mobility and short‐circuit current density with smaller charge recombination, showing very good agreements with molecular structures and morphological characteristics. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3826–3834 Abstract : Two semicrystalline low band gap polymers based on strong electron‐deficient 2, 1, 3‐benzothiadiazole‐5, 6‐dicarboxylicimide (BTI) were synthesized by considering the chain planarity via intrachain noncovalent coulombic interactions. Interestingly, PPDTBTI shows a pronounced edge on packing structure with PCE of 5.47% but PPDTTBTI achieves higher device performance (PCE = 6.78%) which is related to higher J SC and a predominant face on orientation in both pristine and blend films.